AGE RELATED CHANGES IN PHYSIOLOGY OF NORMAL HUMAN TOOTH ENAMEL: A REVIEW - Mansoor, Afsheen; Moeen, Faisal; Hussain, Aleena; Din, Shahab Ud; Khan, Muhammad Talal; Said, Farrukh (Pakistan Journal of Physiology, 2020)
There are usually 32 teeth in adult humans which are separated equally into two arches namely the upper arch (maxilla) and the lower arch (mandible). Dental enamel is the outermost protective layer that aids the tooth in bearing the masticatory forces and helps it endure the harsh oral environment. Age-related changes occur in teeth approximately between ten weeks in utero to old age. Lacassagne in 1889 was the first to characterise changes in fully formed teeth with ageing; however, the first scientific assessment was provided by Gustafson. In 1967, Furuhata and Yamamoto added various phenomenon that may be expedient in defining an age. After twenty-five years of age, they linked an increase in the specific gravity of teeth with age. They further pointed out the process of attrition, which progresses with age, and the components of the tooth namely enamel, dentine, and cementum harden with increasing age. These investigators also defined the decreasing size of the root canals with age. Bodecher and Lefkowitz employed permeability and x-ray studies to indicate maturational effects in the human teeth. Kastelic determined through the incineration studies, an increase, upon a percentage basis, in the organic content of the whole human tooth with age. Ultimately age-related changes in teeth are based on biological markers of age. Teeth reflect the biological or physiological age of the individual and variations caused by genetic factors and chewing habits can influence tooth anatomy. Pak J Physiol 2020;16(3):35–40